Solidaritas Sosial Dalam Ritual Kepercayaan Masyarakat Adat di Desa Juhu Kabupaten Hulu Sungai Tengah - Mi'rajiah; Dimas Asto Aji An’amta; Setia Budhi (Huma: Jurnal Sosiologi, 2023)
Juhu village is a traditional village and maintains belief rituals that have meaning as a binder and controller of the indigenous way of life. The purpose of this study is to analyse rituals that contain social solidarity values in indigenous groups. This research uses a descriptive qualitative approach, with a field research type. The research was conducted in Juhu Village, Batang Alai Timur Sub-district, Hulu Sungai Tengah Regency. Data collection techniques used participant observation, interviews and documentation. The data analysis technique went through the stages of data reduction, data presentation and conclusion drawing. The results showed that the rituals performed by indigenous people in Juhu Village are a form of expressing gratitude to the guardians of the forest, as well as their respect for the spirits of ancestors. The form of respect results in rituals that are believed and still consistently performed by the community. The famous rituals are puja tampa, puja kariwaya, farming ritual, marriage ritual and death ritual. In the implementation of rituals, there are values that can control the social life of the people of Juhu Village. The existing values produce a community order that has strong emotional bonds. The emotional bonds are naturally built due to the similar responsibilities of each member of the community. In addition, the indigenous people in Juhu Village are able to fulfil their needs independently, so they are not so dependent on the outside community. Overall, it can be said that the indigenous community in Juhu Village is a community bound by mechanical solidarity.